Hydrodynamics of Underwater Gas Explosion in Half-Closed Chamber Situated in Well - V. V. Ivashechkin; V. V. Veremenuk (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers a mathematical model for pulsation process of underwater gas explosion products in a half-close cylindrical rigid chamber during gas-impulse regeneration of filters. Second-order differential equation with constant coefficients has been derived. A special calculation program has been developed to solve the equation. The paper proposes formulae for calculation of pressure impulse, maximum velocity and dimensions of gas cavity during expansion process.